In vitro analysis of carotid lesions using a preliminary microwave sensor to detect vulnerable plaques: Correlation with histology, Duplex ultrasound examination, and computed tomography scanner: The Imaging and Microwave Phenotyping Assessment of Carotid stenosis Threat (IMPACT) study - Rania Shahbaz, PhD; Etienne Charpentier, MD; Maharajah Ponnaiah, PhD; Frédérique Deshours, PhD; Hamid Kokabi, PhD; Isabelle Brochériou, MD, PhD; Gilles Le Naour, PhD; Alban Redheuil, MD, PhD; Fabien Koskas, MD, PhD; Jean-Michel Davaine, MD, PhD (JVS - Vascular Science, 2024)
Objective: Progress in best medical treatment have made identification of best candidates for carotid surgery more difficult. New diagnostic modalities could be helpful in this perspective. Microwaves (MWs) can quantify dielectric properties (complex relative permittivity) of biological tissues and MW technology has emerged as a promising field of research for distinguishing abnormal tissues from healthy ones. We here evaluated the ability of a dedicated MW sensor developed in our laboratory to identify vulnerable carotid lesions. Methods: We included 50 carotid lesions in this study. The plaques were analyzed and classified preoperatively by ultrasound (US) examination, computed tomography angiography and tested postoperatively using a MW sensor. Histopathological analysis was used as a gold standard to separate vulnerable plaques (VPs) from nonvulnerable plaques (NVPs). Results: VPs were more frequently types 2 or 3 plaques (on US examination), had a greater proportion of low (<60 Hounsfield unit) and moderate (60-130 Hounsfield unit) attenuation components (computed tomography angiography) and displayed higher dielectric constant values (MW) than NVPs, which had an opposite profile. NVPs were more frequently asymptomatic plaques compared with VPs (P = .035). Multivariate analysis showed that US examination and MW identified VPs with a sensitivity of 77% and a specificity of 76% (cutoff value, –0.045; area under the curve, 0.848; P < .0001). Conclusions: We found that the presence of types 2 to 3 (on US examination) and high dielectric constant plaques in vitro was highly indicative of a VP based on histological analysis. Further studies are needed to determine the potential of MW to identify the most dangerous asymptomatic carotid lesions.